Preventing student drop out through supply chain management process: a focus on Directorate of Primary Education, Bangladesh - Talukder, Md. Jahangir Hossain (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.